The great Santa stakeout - Bird, Betsy (Arthur A. Levine Books, an imprint of Scholastic, Inc., 2019)
Freddy Melcher is obsessed with Santa Claus: he has posters, clothes, underwear, action figures, everything but a photograph of the real Santa--and though it will take planning, trip wires, and staying awake late, this year he is determined to get the ultimate selfie.